Validation of a Multidimensional Spiritual Guidance Intensity Instrument: Examining Content Validity Using Aiken's V and Likert-Based Item Analysis - Abdul Karim; Agus Riyadi; Adi Slamet Kusumawardana (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
This study examines the content validity of the spiritual guidance intensity instrument through expert judgment from five Islamic counseling and psychology experts. A total of 48 items were analyzed using Aiken's V formula. The results showed that 39 items (81.25%) were declared acceptable and 9 items (18.75%) were acceptable with minor revisions, indicating good content validity for the entire instrument. This indicates that all items have good content validity and are suitable for use. This study confirms that behavioural and observable dimensions tend to have higher and more consistent content validity than experiential or transformational dimensions. Theoretically, this study contributes to the development of spiritual guidance measurement instruments with an evidence-based approach through content validation. This study is the first to test the feasibility of spiritual guidance intensity instruments based on expert judgement.